Dally regulates Dpp morphogen gradient formation in the Drosophila wing. - Fujise, M.; Takeo, S.; Kamimura, K.; Matsuo, T.; Aigaki, T.; Izumi, S.; Nakato, H. (Development, 2003)
Decapentaplegic (Dpp), a Drosophila TGF beta/bone morphogenetic protein homolog, functions as a morphogen to specify cell fate along the anteroposterior axis of the wing. Dpp is a heparin-binding protein and Dpp signal transduction is potentiated by Dally, a cell-surface heparan sulfate proteoglycan, during assembly of several adult tissues. However, the molecular mechanism by which the Dpp morphogen gradient is established and maintained is poorly understood. We show evidence that Dally regulates both cellular responses to Dpp and the distribution of Dpp morphogen in tissues. In the developing wing, dally expression in the wing disc is controlled by the same molecular pathways that regulate expression of thick veins, which encodes a Dpp type I receptor. Elevated levels of Dally increase the sensitivity of cells to Dpp in a cell autonomous fashion. In addition, dally affects the shape of the Dpp ligand gradient as well as its activity gradient. We propose that Dally serves as a co-receptor for Dpp and contributes to shaping the Dpp morphogen gradient.